2017
DOI: 10.11113/mjfas.v13n4-2.843
|View full text |Cite
|
Sign up to set email alerts
|

The effect to flow rate characteristic on biodegradation of bone scaffold

Abstract: This paper proposes an improved modeling approach for bone scaffolds biodegradation. In this study, the numerical analysis procedure and computer-based simulation were performed for the bone scaffolds with varying porosities in determining the wall shear stresses and the permeabilities along with their influences on the scaffolds biodegradation process while the bio-fluids flow through within followed with the change in the flow rates. Based on the experimental study by immersion testing from 0 to 72 hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
13
2
Order By: Relevance
“…The bone scaffold with high permeability will be better in the regeneration process [7]. In this present study, the permeability was lower than the previous work of [20]. Figure 8 showed that specimen C (55% of porosity) was the highest permeability compare to the specimen A (30% of porosity) and B (41% of porosity).…”
Section: Relationship Between Permeability and Porosity Of The Bone Scontrasting
confidence: 54%
See 4 more Smart Citations
“…The bone scaffold with high permeability will be better in the regeneration process [7]. In this present study, the permeability was lower than the previous work of [20]. Figure 8 showed that specimen C (55% of porosity) was the highest permeability compare to the specimen A (30% of porosity) and B (41% of porosity).…”
Section: Relationship Between Permeability and Porosity Of The Bone Scontrasting
confidence: 54%
“…The cross-section with a higher exposed surface area generated lower shear stress compared to the low exposed surface area. From the previous work conducted by [20,21] , the shear stress obtained was 0.12 x 10 -5 Pa -5.74 x 10 -5 Pa. In this study, the value of shear stress obtained is higher than the value of the shear stress of the previous study, this can occur due to different boundary conditions and method of analysis.…”
Section: Shear Stresses On Samples Before and After Degradationcontrasting
confidence: 46%
See 3 more Smart Citations